Combined antimicrobial effect of oregano essential oil and caprylic acid in minced beef - Hulankova, Radka; Borilova, Gabriela; Steinhauserova, Iva (Meat science, 2013)
Oregano essential oil (OEO) and caprylic acid (CA) are highly aromatic natural antimicrobials with limited individual application in food. We proved their combined additive effect when used in meat. Application of 0.5% CA and 0.2% OEO (v/w) with 0.1% of citric acid in vacuum packed minced beef inoculated with Listeria monocytogenes at a concentration of 5 log cells/g reduced counts of lactic acid bacteria by 1.5 log CFU/g and counts of psychrotrophic bacteria and L. monocytogenes by more than 2.5 log CFU/g at the end of storage at 3°C for 10 days. In sensory evaluation the samples with OEO showed during the whole experiment statistically better scores than control, whereas the samples treated with CA showed worse colour attributes.
Keywords: Cattle; Odorants; Animals; Food Microbiology; skot; Listeria monocytogenes; Origanum; Hydrogen-Ion Concentration; barva; vakuum; oleje prchavé; Food Contamination; kapryláty; obaly potravin; konzervace potravin; antiinfekční látky; lidé; maso; počet mikrobiálních kolonií; Anti-Infective Agents; Food Preservation; chemické jevy; Meat; Color; Vacuum; odoranty; Colony Count, Microbial; Chemical Phenomena; Oils, Volatile; dobromysl (rod); potravinářská mikrobiologie; kontaminace potravin; Consumer Product Safety; Food Packaging; Lactobacillaceae; Caprylates; spotřebitelská bezpečnost produktů; zvířata; koncentrace vodíkových iontů; Humans